THE FREQUENCY OF DIFFERENT CAUSES OF PREDOMINANT MOTOR NEUROPATHY IN PATIENTS PRESENTING AT TERTIARY CARE HOSPITAL - KUMARI , W; DAS , T; DAS , A; RANA , JS; LAKHAIR , M; IRFAN , M (Biological and Clinical Sciences Research Journal, 2024)
Predominant motor neuropathy (PMN) encompasses a variety of neuropathies primarily affecting motor nerves, leading to muscle weakness and functional impairment. Identifying the causes of PMN is crucial for diagnosis and treatment planning. Objective: The present study aims to determine the frequency of different causes of predominant motor neuropathy in patients at a tertiary care hospital. Methods: This cross-sectional study was conducted at the Department of Neurology, Civil Hospital Karachi, from March 27, 2022, to September 27, 2022, following ethical approval from the institutional review board. A total of 139 patients aged 15-70 years, of either sex, diagnosed with PMN were included through non-probability consecutive sampling. Patients with predominant sensory neuropathy or mixed neuropathies were excluded. Data were analyzed using statistical methods to determine the frequency of various causes of PMN, with particular attention to gender and diabetes status. Results: The most frequent cause of neuropathy was Acute Motor Axonal Neuropathy (AMAN) (26.6%), followed by Acute Inflammatory Demyelinating Polyneuropathy (AIDP) (21.58%), Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) (19.4%), and Charcot-Marie-Tooth disease (16.5%). Less common causes included multifocal motor neuropathy (8.6%), porphyria (3.6%), lead intoxication (2.88%), and familial amyloid neuropathy type 2 (0.7%). There were significant differences in the frequency of neuropathy causes based on gender (p = 0.011) and diabetes status (p = 0.006). Conclusion: The study identified Acute Motor Axonal Neuropathy as the most frequent cause of predominant motor neuropathy, followed by Acute Inflammatory Demyelinating Polyneuropathy. These findings underscore the importance of recognizing specific causes of PMN for appropriate management.